Comparison of the Effect of Lidocaine Adding Dexketoprofen and Paracetamol in Intravenous Regional Anesthesia. (31st March 2014) - Akdogan, Ali; Eroglu, Ahmet
Abstract : Objective. Comparison of dexketoprofen and paracetamol added to the lidocaine in Regional Intravenous Anesthesia in terms of hemodynamic effects, motor and sensorial block onset times, intraoperative VAS values, and analgesia requirements. Method. The files of 73 patients between 18 and 65 years old in the ASA I-II risk group who underwent hand and forearm surgery were analyzed and 60 patients were included in the study. Patients were divided into 3 groups: Group D (n = 20 ), 3 mg/kg 2% lidocaine and 50 mg/2 mL dexketoprofen trometamol; Group P (n = 20 ), 3 mg/kg 2% lidocaine and 3 mg/kg paracetamol; Group K (n = 20 ), 3 mg/kg 2% lidocaine. Demographic data, motor and sensorial block times, heart rate, mean blood pressure, VAS values, and intraoperative and postoperative analgesia requirements were recorded. Results. Sensorial and motor block onset durations of Group K were significantly longer than other groups. Motor block termination duration was found to be significantly longer in Group D than in Group K. VAS values of Group K were found higher than other groups. There was no significant difference in VAS values between Group D and Group P. Analgesia requirement was found to be significantly more in Group K than in Group P. There was no significant difference between the groups in terms of heart rates and mean arterial pressures. Conclusion. We concluded that the addition of 3 mg/kg paracetamol and 50 mg dexketoprofen to lidocaine as adjuvant in Regional Intravenous Anesthesia applied for hand and/or forearm surgery created a significant difference clinically.